Daily Report from the California Democratic Delegation (1968)
This pre-convention "Daily Report" from the California Democratic Delegation, dated August 25, 1968, welcomes delegates to Chicago and outlines opening events for the week. It announces a Sunday evening caucus for California delegates and alternates, followed by a reception and supper hosted by the delegation at the La Salle Hotel. The report highlights a full schedule of social and political activities organized under Adele Leopold, including access to the California Delegation Lounge and city tours. It also provides contact information for the McGovern, McCarthy, and Humphrey campaign headquarters located in major convention hotels. Finally, it notes uncertainty about the precise convention agenda but anticipates opening ceremonies Monday evening and platform and credentials debates on Tuesday.